Growth and Development of Religious Souls in Children Aged 8-10 Years - Izzatunnisa Izzatunnisa; Ramadhan Lubis; Saidatul Fadilla Nasution; Sindi Antika; Azizi Anggi Utami; Muhammad Fathoni (Pusdikra-Publishing.com, 2023)
This research discusses the development of religious spirit in children aged 8-10 years in the context of the Islamic religion. Through a qualitative approach, this research uses in-depth interviews with an 8 year old girl named Aqila Kanza, to understand her level of spiritual development. The research results show that Aqila Kanza is at an early stage of religious development, where she accepts religious beliefs from her parents and environment without deep understanding. Nevertheless, he showed seriousness in studying and carrying out worship in the Islamic religion. This research highlights the important role of parents in guiding children in aspects of their religion and provides insight into the development of a religious spirit in children of the same age.